2007
DOI: 10.1074/jbc.m704314200
|View full text |Cite
|
Sign up to set email alerts
|

A Caspase-3-cleaved Fragment of the Glial Glutamate Transporter EAAT2 Is Sumoylated and Targeted to Promyelocytic Leukemia Nuclear Bodies in Mutant SOD1-linked Amyotrophic Lateral Sclerosis

Abstract: EAAT2 (excitatory amino acid transporter 2) is a high affinity, Na؉ -dependent glutamate transporter of glial origin that is essential for the clearance of synaptically released glutamate and prevention of excitotoxicity. During the course of human amyotrophic lateral sclerosis (ALS) and in a transgenic mutant SOD1 mouse model of the disease, expression and activity of EAAT2 is remarkably reduced. We previously showed that some of the mutant SOD1 proteins exposed to oxidative stress inhibit EAAT2 by triggering… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
86
3

Year Published

2009
2009
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 82 publications
(93 citation statements)
references
References 62 publications
3
86
3
Order By: Relevance
“…Other reports in the literature, however, showed that the loss of the glutamate-transporter EAAT2 in the mouse and rat models of ALS occurs also at presymptomatic and early symptomatic stages of the disease when no overt loss of motor neurons has occurred, suggesting perhaps that additional mechanisms could be responsible for the selective loss of EAAT2, independent of neuronal inputs (54,68,114). In the SOD1-G93A rat model of ALS, focal loss of the EAAT2 glutamate transporter in the ventral horn of the spinal cord coincides with gliosis, but appears before motor neuron=axon degeneration.…”
Section: Foran and Trottimentioning
confidence: 92%
See 2 more Smart Citations
“…Other reports in the literature, however, showed that the loss of the glutamate-transporter EAAT2 in the mouse and rat models of ALS occurs also at presymptomatic and early symptomatic stages of the disease when no overt loss of motor neurons has occurred, suggesting perhaps that additional mechanisms could be responsible for the selective loss of EAAT2, independent of neuronal inputs (54,68,114). In the SOD1-G93A rat model of ALS, focal loss of the EAAT2 glutamate transporter in the ventral horn of the spinal cord coincides with gliosis, but appears before motor neuron=axon degeneration.…”
Section: Foran and Trottimentioning
confidence: 92%
“…Moreover, we found that CTE-SUMO1 accumulates in the nucleus of astrocytes, where it interacts with promyelocytic leukemia protein (PML) in nuclear structures called PML-nuclear bodies (PML-NBs) (54). Several lines of evidence indicate that SUMOylation of polypeptides and proteins can affect protein stability, protein-protein interactions, subcellular relocalization, and transcriptional regulation (61), and that PML-NBs interact with chromatin to regulate gene expression and DNA repair and transcription (55).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Using Western blotting, we observed that each of the four isoforms, whether tagged or not, showed a predominant broad band of molecular weight of approximately 75 kDa, which sometimes appears as a doublet, corresponding to the monomer. The presence of a range of bands of approximately this size may be due to variations in post-translational modification and/or proteolysis of GLT-1 (Danbolt 2001;Boston-Howes et al, 2006;Gibb et al, 2007). As well as monomeric GLT-1, all constructs and endogenous GLT-1 show a cluster of immunoreactive bands with molecular masses of Ͼ180 kDa.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, oxidative stress was shown to activate caspase-3, resulting in a cleavage of EAAT2 in the cytosolic C-terminal domain. This result suggested a functionally important role of the C terminus and linked excitotoxicity and activation of caspase-3 as converging mechanisms in the pathogenesis of ALS (24,25).…”
mentioning
confidence: 87%